Pelatihan Pembuatan Pewarna Alami Daun Ketapang, Daun Jarak dan Daun Jambu Biji Sebagai Bahan Dasar Pembuatan Eco Print Teknik Iron Blanket - Arina Haq; Ariyana Damayanti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
Indonesia is a country that is rich of high value natural resources, one of them is its tropical climate that makes various types of plants easily grow. The various types of trees have their respective uses, especially in the fashion sector. Some trees in a part being used as natural textile dyes, which the existence can be easily obtained. Catappa leaves, guava leaves and castor leaves are plants that can be used as natural dyes in making Eco print iron blanket technique. The purpose of this training is to broaden the students’ knowledge, especially Cut Nyak Dien Vocational School students, in the Fashion Design program. Which can be used as an opportunity to start a business, later. The method used is by providing a training in making natural dyes from Catappa leaves, guava leaves and castor leaves in making Eco print iron blanket technique. This training produces fabric products with patterns and colors obtained from natural dyes using the iron blanket technique. Eco print products using natural dyes, Catappa leaves, guava leaves and castor leaves can be an alternative business opportunity which is environmentally friendly and a popular product.